Employment adjustments following rises and reductions in minimum wages: New insights from a survey experiment - Mario Bossler; Michael Oberfichtner; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2018)
The effects of large minimum wage increases, like those planned in the UK and in some US states, are still unknown. We conduct a survey experiment that randomly assigns increases or decreases in minimum wages to about 6,000 plants in Germany and asks the personnel managers about their expectations concerning employment adjustments. We find that employment reacts asymmetrically to positive and negative changes in minimum wages. The larger the increase in the minimum wage is, the larger the expected reduction in employment. Employment adjustments are more pronounced in those industries and plants which are more strongly affected by the current minimum wage and in those plants that have neither collective agreements nor a works council. In contrast, employment is not found to increase if the minimum wage is reduced by about 10 percent. This mainly reflects that plants with works councils and collective agreements would not cut wages. – – Die Auswirkungen von starken Anhebungen der Mindestlöhne, wie sie in Großbritannien und einigen US-Staaten geplant sind, sind noch uner-forscht. Wir führen ein Befragungsexperiment durch, das rund 6000 Betrieben in Deutschland zufällig Erhöhungen oder Senkungen von Mindestlöhnen zuweist und die Personalverantwortlichen nach den zu erwartenden Beschäftigungsanpassun-gen fragt. Es zeigt sich, dass die Beschäftigung asymmetrisch auf positive und negative Mindestlohnänderungen reagiert. Je stärker der Mindestlohn steigt, desto größer ist der erwartete Beschäftigungsrückgang. Beschäftigungsanpassungen fallen in denjenigen Branchen und Betrieben größer aus, die stärker vom derzeitigen Mindestlohn betroffen sind, sowie in denjenigen Betrieben, die weder Tarifverträge noch Betriebsräte haben. Im Gegensatz dazu nimmt die Beschäftigung nicht zu, falls der Mindestlohn um ca. 10 Prozent gesenkt wird. Dies hängt vor allem damit zusammen, dass Betriebe mit Betriebsräten und Tarifverträgen die Löhne nicht kürzen würden.
Keywords: J31; J23; D22; 330; minimum wage; wage cuts; establishment survey; Germany